The Effectivity of Murottal Al-Qurâ€™an Exposure to Spermatogenesis of Male Mice (Mus musculus) with stress - Dianti, Meilina Ratna; Mazidah, Lilik Khoiriyatul; Ari Indrawijaya, Yen Yen; Inayatilah, Fidia Rizkiah (Journal of Islamic Medicine, 2021)
Introduction: Stress is the body's reaction to pressure from stressors; one of the stressors that can trigger stress is a noise stressor. Stress can disrupt the body's homeostasis system, one of the cycles of spermatogenesis. Murottal Al-Qur'an therapy listening can produce a response of relaxation and peace of mind to increase healing. Methods: The study was conducted on 25 healthy male mice aged 8-12 weeks grouped randomly into five groups. The positive control group is the normal group. The negative control group is given a 12-hour stressor. The treatment groups are given 12 hours and 1, 2, and 4 hours therapy. The treatment for each group was carried out for 21 days. Spermatogenesis of mice was observed through the number of primary spermatocytes cells and spermatid cells. It takes place during the preparation of testicular histology with Hematoxylin Eosin staining. Primary spermatocyte and spermatid counts were examined under a 40x magnification microscope. Results: Murottal Al-Qur'an therapy can affect the amount of primary spermatocyte cells (p-value = 0.000) and spermatids (p-value = 0,000) that are very significant. Conclusion: Murottal Al-Qur'an therapy can be used to increase the spermatogenesis of mice with stress.Â Keywords: Stress, Noise, Spermatogenesis, Murottal Al-Qur'an.